Continuing education of teachers: technical rationality versus professional development - Gasparelo, Rayane Regina Scheidt; Schneckenberg, Marisa (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2017)
This test emerged from theoretical reflections, with the aim of highlighting the main debates conceptual and methodological to the proposition of continuous education of teachers in recent years. Pérez-Gómez (1995) noted that teacher training is determined by the design of school, teaching and curriculum used throughout history, and that there are two basic conceptions in the form of designing educational interventions, and specifically the activity of teachers as a professional education, responsible for the nature and quality of daily educational in the classroom and in school, they are: the teacher as a technical-specialist or the teacher as reflective practice that examines and discusses its own action. Therefore, the technical perspective and the perspective of professional development are the cornerstones that mark the field of discussion about continued education.